Sociofamiliarity of the patient with schizophrenia (Research, Society and Development, 2020)
This study aimed to analyze the different obstacles and difficulties that a family faces when it has a schizophrenic carrier in the home, and how nursing can collaborate with the treatment and improvement in their quality of life. It is an exploratory, descriptive, integrative literature review (RIL) type study. For data collection, the virtual research libraries SciELO, LILACS, PubMed and Google Academic were used, applying eligibility and ineligibility criteria for the selection of publications. The results showed that family members living with schizophrenia have difficulties to understand the disorder, identify and deal with crises generating a certain overload, both to the patient and the caregiver, making it necessary that the nursing team welcomes these families providing information about the disorder, establishing a positive impact on family members and patient, consequently generating improvement for the patient and family, because it is extremely important a healthy social coexistence to improve the clinical picture of the patient with schizophrenia, along with treatment with the multidisciplinary team. It is concluded that the relationship between the nursing team and family members of schizophrenia patients is shared through the feelings and emotions generated by the experience between them. By providing information and carrying out the welcome, the nursing team can establish a relationship that has a positive impact on family members, which can be one of the consequences of improving patient care. Through the nursing staff, it is possible to reflect on the insertions, movements and interactions established between them and the schizophrenic patient.